2010
DOI: 10.1021/jp103745g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Assisted Dispersion of Pristine Multiwalled Carbon Nanotubes in Aqueous Media

Abstract: Graphene oxide (GO) sheets, considered as “soft” two-dimensional macromolecules containing multiple aromatic regions and hydrophilic oxygen groups, can adsorb the pristine multiwalled carbon nanotubes (MWNTs) through the π-stacking interaction, thus causing pristine MWNTs to stably disperse and fractionate in aqueous media. The water-soluble and insoluble complexes can be obtained by changing the initial proportion of MWNTs to GO sheets, which are important for noncovalent approaches toward solubilizing CNTs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(210 citation statements)
references
References 51 publications
10
196
1
3
Order By: Relevance
“…This is most likely due to the increase in MWNTs overcoming the stabilizing effect of the GO. The UV-vis spectrum of a GO solution ( Figure 1) shows a peak centred at a maximum wavelength of 227 nm, indicating π -π transitions of aromatic C-C bonds while a shoulder peak at 300 nm can be assigned to n -π transitions of C=O bonds ( Figure 1a) that correspond to previously published results [5,9,13].…”
Section: Go/mwnts Dispersionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is most likely due to the increase in MWNTs overcoming the stabilizing effect of the GO. The UV-vis spectrum of a GO solution ( Figure 1) shows a peak centred at a maximum wavelength of 227 nm, indicating π -π transitions of aromatic C-C bonds while a shoulder peak at 300 nm can be assigned to n -π transitions of C=O bonds ( Figure 1a) that correspond to previously published results [5,9,13].…”
Section: Go/mwnts Dispersionsupporting
confidence: 84%
“…This dispersion was purified as per the method reported by Zhang [13] as follows. The dispersion was centrifuged for 30 min at 8000 rpm to remove the unstabilized MWNTs, followed by centrifugation at 14000 rpm for 20 min to separate the GO/MWNTs from excess GO.…”
Section: Synthesis Of Graphene Oxide/ Mwnts Composite (Go/mwnts)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have established that graphene oxide could work as an efficient surfactant to disperse CNTs and therefore uniform mixture of CNTs and graphene could be prepared. [63] When prepared as flexible electrodes, such composites generally have better performance than either of CNTs or graphene alone, and a remarkable specific capacitance of 265 F/g was achieved for electrodes with 16 wt% of multiwalled carbon nanotubes (Figure 4). [37] In another similar study, 326 F/g was obtained for composite electrodes with 10% CNTs, which is also substantially higher than pure CNTs and graphene electrodes.…”
Section: Flexible Electrodes Based On Composite Carbonmentioning
confidence: 99%
“…Therefore, the aggregation problem of GO and CNTs has to be resolved in order to move the field forward. In recent years, it was found that the dispersion of CNTs/GO hybrid in solution media can be improved by ultrasonication [3,4]. Moreover, the chemical functionalization was proved to provide better long-term stability and better dispersibility [5].…”
Section: Introductionmentioning
confidence: 99%